Mimicry and Hybridity of â€œCongrock Musik 17â€ in Semarang (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
Keroncong, a slow and crooning music, serves as the art and culture that reflects Indonesian identities. This music style still exists today, particularly in Semarang that is widely known as an urban area. The resistance of such music is actualized with the process of mimicry and hybridity of keroncong and rock music, causing pros and cons that lead to a crisis. The performed mimicry and hybridity is a negotiation in identity construction that takes place in ambivalent behavior as a strategy to survive from the crisis. Building an identity of Congrock (keroncong and rock) is carried out to explore the mediation form in the third space, enabling the outlining of the position of Congrock identity in Semarang. A case study, an art research method, and historical reading were employed to interpret the existing phenomenon. The result indicated that the Congrock identity was the result of mimicry and hybridity that was formed due to the hegemony in Indonesia. Mimicry and hybridity had become the most important point because they took place in an urban area, such as Semarang. The integration of local and global cultures in Congrock generated a new identity in society as the third space and created a gray zone in Congrock, i.e., the area between the form of imitation and cross-cultural music integration. The position of Congrock in Semarang became a symbol of freedom in negotiating locality while partially articulating modernity.